STRATEGI PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN PARTISIPASI SISWA DI SMA NEGERI 1 PANYABUNGAN SELATAN - Garang, Abdullah; Muhammad Fahri; Nuralya Fitri; Nur Hikmah; Rahmat Muhaimin; Riyadotul Jannah; Ade Arga Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student participation is a crucial factor in the success of the learning process. However, in classroom learning practices, low student engagement is often found due to teacher dominance and the use of teacher-centered learning methods. This condition results in low student engagement in critical thinking, discussions, and expressing opinions. This study aims to explain active learning strategies to increase student participation in class. The research method used is a literature review by analyzing various scientific sources in the form of books and journal articles relevant to the concept and application of active learning. The results of the study indicate that the application of active learning strategies, such as group discussions, question and answer sessions, problem-based learning, and group work, can increase student engagement cognitively, affectively, and socially. Students become more active in asking questions, expressing opinions, working together, and are more motivated in participating in learning. In addition, active learning also contributes to increased student understanding of the subject matter. Thus, active learning strategies can be used as an effective solution to increase student participation and create meaningful and student-centered learning.